Analisis Selektivitas Senyawa Turunan Diosmetin Sebagai Antioksidan Baru dengan menggunakan Metode MolecularDocking - Martati, Titiek; Mumpuni, Esti; Mulatsari, Esti; Maryanto, Kenny (Jurnal Farmasi Indonesia, 2018)
Free radicals are compounds that have nofree electron pair, so it ws unstable and too reactive, to be able to ward off free radicals, required an antioxidant. Antioxidant can prevent the occurrence of oxidative reactions that can cause various diseases. The commonly used antioxidant compounds are vitamin C, vitamin E, and flavonoids. One of flavonoid compound that have the potential to be developed into antioxidants is diosmetin. The results of the study using the QSAR method, state that some of diosmetin derived compounds have better antioxidant activity than diosmetin. In this research, the selectivity of diosmetin derived compounds in several enzymes as an antioxidant was tested by using molecular docking methods. Software used for molecular docking were PLANTS, YASARA, MarvinSketch. This study used 15 diosmetin derived compounds, diosmetin as a parent compound, and comparison compounds used were vitamin C, vitamin E, and quercetin. Validated target proteins are 7 (seven) receptors with PDB codes 1QQW, 1V4S, 1XAN, 2BEL, 2C9V, 4K7O, and 5M2F. The results of this study have obtained the best selective compounds to receptors and compounds in each receptor. The best compounds are 6,8-difluoro diosmetin (1QQW), 8-amine diosmetin (1V4S), 6.8-difluoro diosmetin (1XAN), 6.8-diamine diosmetin (2BEL), 5'-amine diosmetin ( 2C9V), 5'-amine diosmetin (4K7O), and 8-amine diosmetin (5M2F). Free radicals are compounds that have nofree electron pair, so it ws unstable and too reactive, to be able to ward off free radicals, required an antioxidant. Antioxidant can prevent the occurrence of oxidative reactions that can cause various diseases. The commonly used antioxidant compounds are vitamin C, vitamin E, and flavonoids. One of flavonoid compound that have the potential to be developed into antioxidants is diosmetin. The results of the study using the QSAR method, state that some of diosmetin derived compounds have better antioxidant activity than diosmetin. In this research, the selectivity of diosmetin derived compounds in several enzymes as an antioxidant was tested by using molecular docking methods. Software used for molecular docking were PLANTS, YASARA, MarvinSketch. This study used 15 diosmetin derived compounds, diosmetin as a parent compound, and comparison compounds used were vitamin C, vitamin E, and quercetin. Validated target proteins are 7 (seven) receptors with PDB codes 1QQW, 1V4S, 1XAN, 2BEL, 2C9V, 4K7O, and 5M2F. The results of this study have obtained the best selective compounds to receptors and compounds in each receptor. The best compounds are 6,8-difluoro diosmetin (1QQW), 8-amine diosmetin (1V4S), 6.8-difluoro diosmetin (1XAN), 6.8-diamine diosmetin (2BEL), 5'-amine diosmetin ( 2C9V), 5'-amine diosmetin (4K7O), and 8-amine diosmetin (5M2F). Free radicals are compounds that have nofree electron pair, so it ws unstable and too reactive, to be able to ward off free radicals, required an antioxidant. Antioxidant can prevent the occurrence of oxidative reactions that can cause various diseases. The commonly used antioxidant compounds are vitamin C, vitamin E, and flavonoids. One of flavonoid compound that have the potential to be developed into antioxidants is diosmetin. The results of the study using the QSAR method, state that some of diosmetin derived compounds have better antioxidant activity than diosmetin. In this research, the selectivity of diosmetin derived compounds in several enzymes as an antioxidant was tested by using molecular docking methods. Software used for molecular docking were PLANTS, YASARA, MarvinSketch. This study used 15 diosmetin derived compounds, diosmetin as a parent compound, and comparison compounds used were vitamin C, vitamin E, and quercetin. Validated target proteins are 7 (seven) receptors with PDB codes 1QQW, 1V4S, 1XAN, 2BEL, 2C9V, 4K7O, and 5M2F. The results of this study have obtained the best selective compounds to receptors and compounds in each receptor. The best compounds are 6,8-difluoro diosmetin (1QQW), 8-amine diosmetin (1V4S), 6.8-difluoro diosmetin (1XAN), 6.8-diamine diosmetin (2BEL), 5'-amine diosmetin ( 2C9V), 5'-amine diosmetin (4K7O), and 8-amine diosmetin (5M2F).